Gambaran Kejadian Ikutan Pasca Imunisasi (KIPI) Covid-19 pada Individu dengan Komorbid Diabetes Mellitus - Zulmah Astuti; Awang Dharma Ericsya; Faried Rahman Hidayat (Jurnal Gema Keperawatan, 2023)
Patients with diabetes mellitus have a fairly high risk of worsening their condition when experiencing Covid-19. This is because individuals are more susceptible to exposure to streptococcal infections, which cause pneumonia, which is a serious complication of respiratory tract problems when exposed to Covid-19. To reduce the impact of these complications, a strategy is needed to increase the immunity of individuals with comorbid diabetes mellitus through the Covid-19 vaccination. The implementation of this vaccination can give a different response to each individual recipient and depends on many factors, including the presence of a previous disease such as diabetes mellitus. The purpose of this study was to get an overview of Covid-19 post-immunization follow-up events (AEFI) in individuals with comorbid diabetes mellitus. This research method is cross-sectional with a purposive sampling technique. The study was conducted on 299 adult respondents who had comorbid diabetes mellitus and received the Covid-19 vaccination. The results of the study obtained data showed that as many as 65 (11,2%) respondents reported not having AEFI symptoms; local symptoms experienced by respondents were swelling (n. 3; 0,5%) and redness at the injection site (n. 1; 0,2%); systemic symptoms experienced by respondents were cramps or muscle pain (n. 104; 17,9%); dizziness (n. 100; 17,2%); fever (n. 99; 17,1%); and drowsiness (n. 93; 16,0%). The degree of AEFI in respondents who had mild symptoms was 93 (16,04%), and moderate symptoms were 422 (72,76%). None of the respondents experienced severe symptoms. Based on these results, it was concluded that the most frequent symptoms were moderate symptoms and systemic symptoms. Even though no severe symptoms are experienced, individual preparation is needed before getting the vaccine to reduce the symptoms of AEFI.